Value of FDG-PET/MR in Oral Focus Assessment in Head and Neck Cancer Patients—A Feasibility Study - Valdec, Silvio; Bosshard, Fabienne A.; Hüllner, Martin; Schwaninger, Dominic R.; Stocker, Larissa; Giacomelli-Hiestand, Barbara; Stadlinger, Bernd (Frontiers in Medicine, 2022)
FDG-PET/MR is a hybrid imaging modality used for the staging and restaging of advanced head & neck cancer (HNC) patients. Their treatment typically involves radiation therapy, which requires previous dental focus assessment. The aim of this study was to analyze if staging FDG-PET/MR is a valuable tool for oral focus assessment. For this purpose, FDG-PET/MR findings, such as metabolic activity of periapical radiolucencies and marginal periodontitis, were retrospectively compared with conventional standardized dental focus assessment, including dental radiographs and clinical assessment of 124 teeth in seven patients. Increased FDG uptake of periapical lesions was found in one out of 23 lesions. Increased FDG uptake of the marginal periodontium was recorded in one out of 34 lesions. In summary, standardized dental focus assessment by panoramic radiography and periapical radiographs may be enriched by information from FDG-PET/MR, showing active inflammation in dental foci. However, many dental foci have no correlate in FDG-PET/MR. The treatment decision for oral foci may benefit from the visualized presence or absence of metabolic activity on FDG-PET/MR.